Thermal destressing: Implications for short-circuiting in enhanced geothermal systems. (January 2023) - McLean, Matthew L.; Espinoza, D. Nicolas
Abstract: Viable Enhanced Geothermal Systems (EGS) require (1) access to large reservoir volumes at high temperatures and (2) sufficient permeability for large production flow rates. However, working fluid injection might quickly decrease the recoverable heat energy. Thermal destressing increases fracture transmissivity and reduces the production temperature. Large fracture openings cause the injection fluid to localize in a single fracture, or a few dominant fractures, and leads to thermal short-circuiting within the EGS hydraulic network. This work provides novel numerical simulations of a multi-fracture EGS that models the fracture aperture from initially closed to mechanically open. Fractures are modeled as discontinuities within a three dimensional thermo-poroelastic rock mass. We derived weak-form equations of mass balance, energy balance, and mechanical contact for fractures and wells and coupled those equations to the Comsol Multiphysics base package. The simulations investigate the full reservoir behavior through coupling of fluid flow through wellbores and fractures with the surrounding rock. Results show that large in-situ stresses contribute to a uniform fluid flow distribution in the fracture network because high compressive contact stresses decrease fracture compressibility and prevent large fracture openings. Initial or late large fracture openings cause thermal short-circuiting and are more likely to arise in locations with low initial stress and compliant fractures. Geometrical and operational properties of the EGS hydraulic network can minimize the severity of thermal short-circuiting including wellbore diameter, fracture spacing, injector/producer lateral spacing, EGS doublet orientation, and number of transmissive fractures. Thermo-mechanical interference between fracture stages causes (1) larger fracture opening displacements and (2) thermal short-circuiting earlier in time. Distinct initial fracture geometries and compliance causes the EGS hydraulic network to flow a non-uniform distribution of the injection fluid from the beginning and tends to decrease heat recovery. Graphical abstract: Highlights: Initially large hydraulic apertures or late re-opening decreases heat recovery. Fractures with high compliance tend to short-circuit. EGS hydraulic network design can minimize the severity of short-circuiting. Thermo-mechanical fracture interaction greatly decreases heat recovery. Heat recovery benefits from homogeneous fracture aperture and high initial stress.